PENINGKATAN EFIKASI GURU KB/TK ‘AISYIYAH NYAI AHMAD DAHLAN DALAM MENGAJARKAN PENCEGAHAN KEKERASAN SEKSUAL PADA ANAK USIA DINI - Khoiryasdien, Andhita Dyorita (Jurnal VARIDIKA, 2020)
Sex education in early childhood is still considered a taboo subject so it has never been taught. Even though children must have enough information in order to protect themselves from sexual harassment and violence. Not only parents, the teacher as the second parent for children has a big role in providing education and information about sexual education. Therefore, as a preventive measure, training is needed to increase the knowledge of teachers about sex education in early childhood and good delivery methods so that it can be easily accepted by children. The method used is lecturing and practice directly with roleplay on how to deliver sex education to children. In addition, roleplay is also done by using puppets. The training participants numbered 22 teachers and employees. After being given training, 77.2% of teachers and staff understood that psychoeducation on the importance of sexual education for children needed to be provided as a preventive measure against the prevention of sexual violence against children. 63.6% of teachers are willing to convey to their students. While the rest claimed to be embarrassed and felt they were not ready to deliver material related to sex education.